2008
DOI: 10.3748/wjg.14.1011
|View full text |Cite
|
Sign up to set email alerts
|

Role of genetic disorders in acute recurrent pancreatitis

Abstract: There was remarkable progress in the understanding of the role genetic risk factors in chronic pancreatitis. These factors seem to be much more important than thought in the past. The rare autosomal-dominant mutations N29I and R122H of PRSS1 (cationic trypsinogen) as well as the variant N34S of SPINK1 (pancreatic secretory trypsin inhibitor) are associated to a disease onset in childhood or youth. Compared to chronic alcoholic pancreatitis the progression is slow so that for a long time only signs of acute-rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0
5

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 21 publications
0
28
0
5
Order By: Relevance
“…It has been reported that mutation in the human equivalent Spink1 gene can lead to chronic pancreatitis (13). This report shows that pancreas-specific expression of the rat PSTI-I protein, which is similar but not identical to the mouse SPINK3 protein, was able to compensate for the absence of SPINK3 in Spink3 Ϫ/Ϫ mice and restore viability in Spink3 Ϫ/Ϫ /TgN(Psti1) mice.…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations
“…It has been reported that mutation in the human equivalent Spink1 gene can lead to chronic pancreatitis (13). This report shows that pancreas-specific expression of the rat PSTI-I protein, which is similar but not identical to the mouse SPINK3 protein, was able to compensate for the absence of SPINK3 in Spink3 Ϫ/Ϫ mice and restore viability in Spink3 Ϫ/Ϫ /TgN(Psti1) mice.…”
Section: Discussionmentioning
confidence: 73%
“…It has been estimated that patients heterozygous for a SPINK1 mutation have a 20-to 40-fold increased risk of developing chronic pancreatitis (13,24). This risk may be as high as 500-fold in individuals with homozygous mutations (13).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hereditary pancreatitis (HP) is an inherited form of chronic pancreatitis characterized by mutations within PRSS1, PRSS2, SPINK1, CFTR and CTRC genes [54,55] . PDAC is often a consequence of this condition [56,57] insomuch so resected pancreata from patients with HP frequently demonstrated PanIN-3 lesions (50%) [58] .…”
Section: Hereditary Pancreatitismentioning
confidence: 99%